Shooting parameters measuring from videostream during sports competitions - Beloyvanov, M. S.; Sadrtdinov, I. A. (MATEC Web of Conferences, 2018)
This paper proposes the method for determining the time and coordinates of hits on targets on the video stream during sports competition. Proposed method allows reduce the number of false alarms of the detector associated with such negative factors at video stream as environment conditions changing, occlusion, video compression artifacts, etc.